Health science research and dimensions from Bench to Bedside - Ahmed , Sadaf; Noushad , Shamoon (International Journal of Endorsing Health Science Research, 2014)
Close incorporation through varied areas of health research and health-care tasks enables researchers, clinicians and scientists to identify how evolving scientific visions can be applied to patient care while carefully assessing new methodologies to preventing, identifying and handling disease through clinical research. A health professional know more about the human body today than we did yesterday, and tomorrow we’ll know even more—a lot more. In the last three decades, advances in human, molecular and genetic areas have sparked a research revolution that reveals ever more detailed and precise information about how human bodies work. Every day brings new discoveries, many of which may hold the potential to improve human health in meaningful ways but the pace at which those discoveries lead to improved health has been disappointingly sluggish. It cannot be denied that new drugs, protocols and therapies do reach patients, and when they do, they often make a tremendous transformation. However, in comparison to the number of research projects conducted, papers published, and trials run, it is clear that new health care advances have lagged behind the vast amounts of data generated by the explosion in biomedical discovery that is unable to facilitate a common man. Pakistan is playing an emerging role among academic medical societies working to change that. On multiple fronts, and in collaboration with world, within the country and nationwide, the researchers and clinicians are exploring ways to increase the haste and efficiency with which research discoveries are rendered into improvements in patient care. Same is the case of drug development, the failure rate is much more with enormous resources and finances expenditure that at the end don’t work for any healthcare concerns.